Approach to the Management of Autoimmunity in Primary Immunodeficiency. (January 2017) - Azizi, G.; Ziaee, V.; Tavakol, M.; Alinia, T.; Yazdai, R.; Mohammadi, H.; Abolhassani, H.; Aghamohammadi, A.
Abstract: Primary immunodeficiency diseases (PIDs) consist of a genetically heterogeneous group of immune disorders that affect distinct elements of the immune system. PID patients are more prone to infections and non‐infectious complications, particularly autoimmunity. The concomitance of immunodeficiency and autoimmunity appears to be paradoxical and leads to difficulty in the management of autoimmune complications in PID patients. Therefore, management of autoimmunity in patients with PID requires special considerations because dysregulations and dysfunctions of the immune system along with persistent inflammation impair the process of diagnosis and treatment.